Dreaming revolution : transgression in the development of American romance - Bradfield, Scott (University of Iowa Press, 1993)
Dreaming Revolution usefully employs current critical theory to address how the European novel of class revolt was transformed into the American novel of imperial expansion. Bradfield shows that early American romantic fiction - including works by William Godwin, Charles Brockden Brown, James Fenimore Cooper, and Edgar Allan Poe - can and should be considered as part of a genre too often limited to the Nineteenth-century European novel. Beginning with Godwin's Caleb Williams, Bradfield describes the ways in which revolution legitimates itself as a means of establishing Political consensus. For European revolutionaries like Godwin or Rousseau, the tyranny of the king must be replaced by the more indisputable authority of human reason. In other words, democratic revolution makes people free to investigate the same truths and arrive at the same democratic conclusions. In the American novel, however, the Enlightenment's idealized pursuit of abstract truth becomes restructured as a pursuit of abstract space. Instead of revealing knowledge, Americans explore further territories, manifest destiny, limitless regions of the yet-to-be-colonized and the still-to-be-known. In a spirited discussion of works by Brown, Cooper and Poe, Bradfield argues that Americans take the class dynamics of the European psychological novel and apply them to the American landscape, reimagining psychological spaces as geographical ones. Class distinctions become refigured in terms of the common people's pursuit of a meaning vaster than themselves - a meaning which leads them to imagine the always expanding body of colonial America. However, since class conflict is never successfully eliminated or forgotten, the memory of class struggle always reemerges in the narrative like a half-repressed dream of politics. In Dreaming Revolution, Bradfield reveals and interprets these dreams, opening these American novels to a richer and more rewarding reading.
Keywords: Cooper, James Fenimore, -- 1789-1851 -- Political and social views.; Poe, Edgar Allan, -- 1809-1849 -- Political and social views.; Brown, Charles Brockden, -- 1771-1810. -- Edgar Huntly.; Godwin, William, -- 1756-1836. -- Things as they are.; Cooper, James Fenimore, -- 1789-1851 -- Pensée politique et sociale.; Poe, Edgar Allan, -- 1809-1849 -- Pensée politique et sociale.; Cooper, James Fenimore, -- 1789-1851; Poe, Edgar Allan, -- 1809-1849; Edgar Huntly (Brown, Charles Brockden); Things as they are (Godwin, William); American fiction -- 19th century -- History and criticism.; Politics and literature -- United States -- History -- 19th century.; Literature and society -- United States -- History -- 19th century.; Revolutionary literature, American -- History and criticism.; Political fiction, American -- History and criticism.; American fiction -- European influences.; Deviant behavior in literature.; Social conflict in literature.; Romanticism -- United States.; Imperialism in literature.; Roman américain -- 19e siècle -- Histoire et critique.; Politique et littérature -- États-Unis -- Histoire -- 19e siècle.; Romantisme -- États-Unis.; Littérature et société -- États-Unis -- Histoire -- 19e siècle.; Littérature révolutionnaire américaine -- Histoire et critique.; Roman américain -- Influence européenne.; Conflits sociaux dans la littérature.; Impérialisme dans la littérature.; Politique-fiction américaine -- Histoire et critique.; Déviance dans la littérature.; LITERARY CRITICISM -- American -- General.; American fiction; American fiction -- European influences; Deviant behavior in literature; Imperialism in literature; Literature and society; Political and social views; Political fiction, American; Politics and literature; Revolutionary literature, American; Romanticism; Social conflict in literature; United States; 1800-1899; Criticism, interpretation, etc.; History